NOTES ON THE LEGAL LIABILITY OF MINING COMPANIES FOR THE PUMPING OF EXTRANEOUS WATER FROM DEFUNCT UNDERGROUND WORKINGS: LEGAL UNCERTAINTIES ILLUSTRATED BY Ezulwini Mining Company Pty Ltd v Minister of Mineral Resources and Energy [2021] ZAGPPHC 4 - Viljoen, Germarie; Rantlo, John; du Plessis, Willemien (Obiter, 2023)
In 2015, the 193 United Nations (UN) member states adopted the UN 2030 Agenda for Sustainable Development, which includes a set of 17 Sustainable Development Goals (SDGs) to be reached by 2030 (UNGA “Transforming Our World: The 2030 Agenda for Sustainable Development” Resolution adopted by the General Assembly (25 September 2015) A/Res/70/1). The SDGs represent a global call for action towards social inclusion, economic development and environmental sustainability. Meeting the SDGs by 2030, however, requires unprecedented cooperation and collaboration among various stakeholders on various levels, ranging from governments, non-governmental organisations and the private sector, including the mining sector. Although it is not the main aim of this contribution to unravel the linkages between the respective SDGs and mining, the country’s mining sector is expected to incorporate relevant SDGs into their operations, business practices and decisions. It is trite that the mining industry, through all its activities and stages, has contributed to many of the challenges that the SDGs set to address, including the displacement of communities, worsening economic and social inequality, and environmental degradation that impacts water security, for example. Nevertheless, in pursuance of the SDGs, South Africa’s mining sector is expected to prioritise the protection of the environment, over exploitation and pollution. In fact, successful advancement of the SDGs also requires substantial and ongoing partnership or collaboration between stakeholders. This is particularly true for interconnected or neighbouring mines, for example. To guide and ensure sustainable and responsible mining, the South African legislature promulgated a comprehensive environmental management and regulatory framework for the country, including the Mineral and Petroleum Resources Development Act (28 of 2002) (MPRDA), the National Environmental Management Act (107 of 1998) (NEMA) and the National Water Act (36 of 1998) (NWA). However, as is discussed in more detail below, regulatory shortcomings, and therefore legal uncertainty, are apparent. This contribution presents the issue of environmental obligations and liabilities to pump extraneous water after mine closure. Naturally, legal uncertainties inherently inhibit the realisation of some of the SDGs, including, for example, SDG 6 (to ensure the sustainable management of water) and SDG 9 (to promote sustainable industrialisation).